Effect of Water Management Practices on Rice Yield, Water Productivity and Water Savings under Irrigated Rice Paddy Ecosystem - Barman, SC; Ali, MA; Hiya, HJ; Sarker, KR; Sattar, MA (Journal of Environmental Science and Natural Resources, 2017)
A field experiment was carried out during the Boro season 2013 to find out the effects of water management practices on rice yield performance and water productivity index at Old Brahmaputra flood plain paddy land, Muktagacha, Mymensingh. The experiment was laid out in randomized complete block design (RCBD) with six (6) irrigation treatments. Two treatments, T1 and T3 were kept under continuous standing water levels (10 cm and 5 cm respectively) while in treatment T5 irrigation water was supplied for 1st 3 weeks then followed mid season drain out and re-flooded at flowering stage. Three alternate wetting and drying irrigation treatments, T2, T4 and T6 were selected in which irrigation water was applied when water level dropped 20cm, 10cm and 15cm below ground level, respectively. All the irrigation treatments significantly affected the rice yield and yield contributing parameters. The study revealed that the highest grain yield (5950 kg ha-1) was found in treatment T5 which was identical with AWDI treatment T4 (5820 kg ha-1) followed by AWDI treatment T6 (5460 kg ha-1). On the contrary, rice yield of 3350 kg ha-1, 4470 kg ha-1 and 4810 kg ha-1 were found in the treatment T1, T2 and T3, respectively. It was found that AWDI treatment T2 showed maximum water savings (15.1%) followed by T6 (11.3%), T4 (7.59%) and T5 (3.8%), however rice yield in the treatment T2 (4470 kg ha-1) was significantly lower compared to T6, T4 and T5 treatment. Therefore, it may be inferred that treatment T4 (AWDI; irrigation when water level fell 10 cm from ground level), T5 (Irrigation for 1st 3 weeks, then mid-season drain out and re-flooding at flowering) and T6 (AWDI; irrigation when water level fell 15cm from ground level) would be the feasible choice for the water savings, higher rice yield as well as maximum water productivity index (0.478, 0.472 and 0.467, respectively) for sustaining rice farming during the dry Boro season in Bangladesh. J. Environ. Sci. & Natural Resources, 9(2): 79-84 2016